Physical Activity and Preschool Social Development: Cultural and Contextual Insights from Indonesia - Ilga Maria; Muhammad Abdul Latif; Rahayu Dwi Utami; Ria Novianti; Asfi Yanti WE (Jurnal Ilmiah Peuradeun, 2026)
This study examines the relationship between digital game exposure, physical activity, and social competence among preschool children in Pekanbaru, Indonesia. While global debates frequently portray screen time as inherently detrimental, limited evidence from Southeast Asian contexts has analyzed how digital engagement and outdoor play jointly influence early social development. Grounded in Vygotsky’s sociocultural theory, this research investigates associations between daily screen time, outdoor physical activity, and children’s expressive, compliant, and disruptive behaviors. A cross-sectional online survey was conducted with 213 parents of children aged 2–5 years. Social competence was measured using the culturally adapted Adaptive Social Behavior Inventory (ASBI), alongside parent-reported screen time and outdoor play duration. Multiple linear regression analyses were applied while controlling for demographic variables. The results indicate that extended screen time is negatively associated with compliant behavior, whereas outdoor physical activity is positively associated with expressive and compliant behaviors. These findings suggest that developmental outcomes depend not merely on digital exposure itself, but on the balance between individualized screen use and socially interactive play. By providing culturally contextualized evidence from Indonesia, this study contributes to a more nuanced understanding of digital childhood in non-Western settings.